Chats About Daily Traffic: Agentic Adaptability of Jabodetabek Commuters to Minimize Stress and Transcend Everyday Lives - Poerwandari, Elizabeth Kristi (UI Scholars Hub, 2020)
With the increasing number of people invading Greater Jakarta and the ongoing improvement of infrastructure in Greater Jakarta or Jabodetabek, one of the challenges faced by the community is traffic congestion. Previous studies revealed the negative impact of traffic congestion on community welfare and mental health. Thus, the present study aims to shed light on how Jabodetabek inhabitants and commuters experience, make sense, and adapt to daily traffic congestion. Data were obtained from discussions in six WhatsApp groups, which included a total of 160 respondents. The study supports the findings of previous studies, that is, traffic congestion leads to increased costs and losses and causes distress. However, the subjective perception of time management enables commuters to adapt to the situation. Nevertheless, the paper presents a novel finding: agentic adaptability of Jabodetabek commuters, which is evidenced by the ability to discover various means of adjusting to traffic congestion. Although effective policies are required to mitigate congestion, the good news is that many opportunities for adjustment await the community in terms of being stuck in traffic.